2018
DOI: 10.4236/ojpsych.2018.82016
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction with Psychiatric Services: A Survey at a Nigerian Federal Teaching Hospital

Abstract: Background: Patient satisfaction, a measure of the extent to which a patient is content with the health care which he or she receives from his or her health care provider, is an effective means of evaluating the performance of a hospital leading to service improvement and attraction of more patients. In a country whose leadership currently calls for change of attitude of the citizenry, it is pertinent to assess how this change has been accepted in health institutions, especially among the most stigmatized grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…Our findings showed that the overall levels of satisfaction among psychiatric inpatients in China were high, with a mean score of 23.3 out of 25. This satisfaction level, which was measured by a different tool from other studies, is in line with surveys of psychiatric inpatients from other countries, such as India [33], Thailand [34], Finland [35], Israel [36], and Nigeria [37]. It is also consistent with a few local surveys of Chinese samples [24, 25].…”
Section: Discussionsupporting
confidence: 87%
“…Our findings showed that the overall levels of satisfaction among psychiatric inpatients in China were high, with a mean score of 23.3 out of 25. This satisfaction level, which was measured by a different tool from other studies, is in line with surveys of psychiatric inpatients from other countries, such as India [33], Thailand [34], Finland [35], Israel [36], and Nigeria [37]. It is also consistent with a few local surveys of Chinese samples [24, 25].…”
Section: Discussionsupporting
confidence: 87%
“…This study found that having secondary and above level education decreases patient satisfaction score by 1.25 units (β = −1:250, 95% CI (-1.765, -0.735), P = 0:000), which was a similar result with the study done in Nigeria [37] and Mekelle [34]; and this similar result might be because those respondents who had higher education had high expectations of service.…”
Section: Psychiatry Journalsupporting
confidence: 82%
“…In that definition, it considers that: “Quality evaluation is an approach that ensures that every patient has a diagnostic and therapeutic approach that ensures the best clinical outcomes in accordance with current medical research, at the best cost, the best results in the least iatrogenic risk and greater satisfaction in terms of treatments, results and human interaction within the healthcare system” [ 10 ]. Patient satisfaction will reflect the efficacy of the healthcare system as it measures the perceived quality of the healthcare provided and must therefore be monitored constantly and frequently [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the nature of medical services, the healthcare industry has a high degree of contact with the patient; researching the factors that affect patient satisfaction plays an important role in the growth of healthcare and in the performance of healthcare providers [ 11 , 12 ]. The findings of such studies are progressively being used by healthcare professionals and regulators to identify and address issues and improve the quality of care [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation